An experimental study on strength and serviceability of reinforced and steel fibre reinforced concrete (SFRC) continuous composite slabs. (1st May 2016) - Gholamhoseini, Alireza; Khanlou, Amir; MacRae, Gregory; Scott, Allan; Hicks, Stephen; Leon, Roberto
Highlights: Sixteen continuous composite slabs were cast with different interface bond. Different types and amounts of steel mesh, fibre or reinforcing bars were used in concrete. Slabs were tested for serviceability and failure load. No end slip occurred under the serviceability load levels. Crack control became effective by increasing fibre dosage to 60 kg/m 3 . Abstract: A comprehensive experimental study was conducted on reinforced and steel fibre reinforced concrete (SFRC) continuous composite slabs to quantify crack width resulting from shrinkage and gravity loading. Sixteen full scale slab specimens were cast with different types of interface bond between the concrete slab and steel decking (e.g. greased, unembossed decking or standard decking) and different types and amounts of reinforcement in concrete (e.g. mesh, steel fibre or normal reinforcing bars). Each slab was continuous over the interior support and had a roller support at each end. Concrete shrinkage was measured and serviceability behaviour of slabs was studied over a period of 90 days. It was found that the shrinkage strains at 98 days of drying in plain concrete samples and samples of fibre-reinforced concrete with dosages up to 40 kg/m 3 were similar. There was no cracking due to the creep and shrinkage-induced strains in the mesh-reinforced or fibre-reinforced composite slabs under their self-weight until 90 days of drying. Subsequently, all the slabs were tested under increasing load until failure. The mid-span deflection and end slip versus applied load were monitored and the crack sizes were obtained for each slab for different levels of applied load. Application of steel fibre in excess of 60 kg/m 3 increased the slip load by 42% and improved crack control significantly as the maximum crack width was often reduced by 50%.